Impact of rs12917 MGMT Polymorphism on [18F]FDG-PET Response in Pediatric Hodgkin Lymphoma (PHL) - Kewitz-Hempel, Stefanie; Kurch, Lars; Cepelova, Michaela; Volkmer, Ines; Sauerbrey, Axel; Conrad, Elke; Knirsch, Stephanie; Pöpperl, Gabriele; Steinbach, Daniel; Beer, Ambros J; Kramm, Christof M; Sahlmann, Carsten-Oliver; et al. (Molecular imaging and biology, 2019)
PURPOSE: The enzyme O6-methylguanine-DNA methyltransferase (MGMT) is an important component of the DNA repair machinery. MGMT removes O6-methylguanine from the DNA by transferring the methyl group to a cysteine residue in its active site. Recently, we detected the single nucleotide polymorphism (SNP) rs12917 (C/T) in the MGMT sequence adjacent to the active site in Hodgkin lymphoma (HL) cell line KM-H2. We now investigated whether this SNP is also present in other HL cell lines and patient samples. Furthermore, we asked whether this SNP might have an impact on metabolic response in 2-deoxy-2-[18F]fluoro-D-glucose positron emission tomography ([18F]FDG-PET), and on overall treatment outcome based on follow-up intervals of at least 34 months. PROCEDURES: We determined the frequency of this MGMT polymorphism in 5 HL cell lines and in 29 pediatric HL (PHL) patients. The patient cohort included 17 female and 12 male patients aged between 4 and 18 years. After characterization of the sequence, we tested a possible association between rs12917 and age, gender, Ann Arbor stage, treatment group, metabolic response following two courses of OEPA (vincristine, etoposide, prednisone, and doxorubicin) chemotherapy, radiotherapy indication, and relapse status. RESULTS: We detected the minor T allele in four of five HL cell lines. 11/29 patients carried the minor T allele whereas 18/29 patients showed homozygosity for the major C allele. Interestingly, we observed significantly better metabolic response in PHL patients carrying the rs12917 C allele resulting in a lower frequency of radiotherapy indication. CONCLUSION: MGMT polymorphism rs12917 seems to affect chemotherapy response in PHL. The prognostic value of this polymorphism should be investigated in a larger patient cohort.
Keywords: Hodgkinova nemoc; Hodgkin Disease; pozitronová emisní tomografie; předškolní dítě; Humans; DNA modifikační methylasy; Tumor Suppressor Proteins; nádorové buněčné linie; nádorové supresorové proteiny; Positron-Emission Tomography; fluorodeoxyglukosa F18; mužské pohlaví; Fluorodeoxyglucose F18; enzymy opravy DNA; sekvence nukleotidů; Child, Preschool; Adolescent; DNA Modification Methylases; ženské pohlaví; jednonukleotidový polymorfismus; lidé; Polymorphism, Single Nucleotide; mladiství; DNA Repair Enzymes; dítě; Child; Male; Cell Line, Tumor; Base Sequence; Female